Effort to Optimize Learning Physics at Integrated Islamic High School via a Physics based Ethnoscience Approach - Koto, Irwan; Setiawan, Iwan; Gunawan, Bodi; Ahda, Netriani Veminsyah; Utama, Tiara Hardyanti; Sari, Klarisa Yulia; Herlambang, Arthur Muhamad Taufan (CV Media Inti Teknologi, 2024)
The aim of community service program is to enhance the educational experience at the integrated Islamic high school (SMA IT Khairu Ummah) Rejang Lebong district by employing an ethnoscience approach. The service program is implemented in SMA IT Khairu Ummah to address challenges posed by inadequate learning facilities and infrastructure, particularly in physics education, which may impede the teaching and learning process. The implementation of community service initiatives in 2024 comprises four phases. The first phase encompasses observational efforts within schools to acquire a comprehensive picture of the educational environment. The second phase involves the socialization of service activities and coordination with school principal and educators, particularly those teaching physics. The third phase entailed instructing educators on the development of ethnoscience-focused educational resources. The last phase entails regular assessment and guidance involving two Mahasiswa Kampus Merdeka Belajar program and five physics lecturers to guarantee that the community service program positively influences the learning process. The findings indicate that the training positively enhances teacher competencies by implementing ethnoscience education that leverages the local community's cultural and traditional diversity, even amidst constraints of limited facilities and infrastructure. Physics teacher and students of SMA IT Khairu Ummah SMA IT have implemented an ethnoscience-based physics approach that is effective in enhancing students' comprehension of scientific processes and their acquisition of related skills.